A time-lapse observational study of the activity patterns and feeding behaviour of urban terrestrial gastropods on carcasses of the Asian house shrew (Suncus murinus) - Liew, Thor Seng; W. K. Fletcher; Ong, Song Quan (Oxford University Press, 2023)
Urban land gastropods, snails and slugs, particularly introduced species, are notorious for causing damage to crops and plants. They are also known for their adaptability and ability to survive in unlikely environments, often feeding on other invertebrates and animal faeces (Speiser, 2001). Despite this, their roles as scavengers on animal carcasses have received relatively little attention in the feeding ecology of land molluscs and forensic science (Galvão et al., 2015).